2018
DOI: 10.1186/s12877-018-0840-1
|View full text |Cite
|
Sign up to set email alerts
|

Geriatric syndromes, multimorbidity, and disability overlap and increase healthcare use among older Chinese

Abstract: BackgroundGeriatric syndromes, multimorbidity, and disability are prevalent among ageing population. However, no study empirically examined their additive or synergistic effect on healthcare use. The present study aims to estimate overlapping prevalence of geriatric syndromes, multimorbidity, and disability; and to examine associations of these three conditions with healthcare use.MethodsA cross-sectional study was conducted in community-dwelling older adults aged 60 and above in 12 Hong Kong districts. Pearso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
54
1
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 70 publications
(62 citation statements)
references
References 26 publications
3
54
1
4
Order By: Relevance
“…Our study showed that the multimorbidity rate of older inpatients was higher among people living in northern areas of China than in the south. Surveys conducted in northern China reported a multimorbidity rate in older adults from 82% to 86.9%, compared with 41.8% to 49.4% in southern China (13,(38)(39)(40). This result could be due to differences in environmental factors and the fact that the lifestyles of older adults in southern China appear to be better than in the north, with people living in southern China having a lower BMI and sodium intake (41).…”
Section: Discussionmentioning
confidence: 99%
“…Our study showed that the multimorbidity rate of older inpatients was higher among people living in northern areas of China than in the south. Surveys conducted in northern China reported a multimorbidity rate in older adults from 82% to 86.9%, compared with 41.8% to 49.4% in southern China (13,(38)(39)(40). This result could be due to differences in environmental factors and the fact that the lifestyles of older adults in southern China appear to be better than in the north, with people living in southern China having a lower BMI and sodium intake (41).…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that very old non-multimorbid patients suffered from severe frailty and had similar healthcare utilization as their multimorbid counterparts did. A local study of community living older people [44] showed that while number of chronic diseases was associated with use of hospital services in the preceding twelve months, geriatric syndromes per se without multimorbidity (such as sarcopenia, frailty, cognitive impairment) also increased use of hospital services to the same extent (increase of approximately 20%). These geriatric syndromes, notably frailty and cognitive impairment, together with a higher risk of medication-related adverse events and other hospital-related complications [45] in older patients might also suffice to explain the generally greater annual number of hospitalized days given the same multimorbidity status [46,47].…”
Section: Discussionmentioning
confidence: 99%
“…It is well-known that older adults often suffer from multi-morbidities. A study showed that among 2618 participants, 75.3%, 41.8%, and 22.5% had geriatric syndromes, multimorbidity, and disability, respectively, and 10.4% had all the three conditions" [8]. Recently, researchers have tried to use model adjustment or mediation analyses to assess possible mediating pathways between HI and cognitive impairment.…”
Section: Introductionmentioning
confidence: 99%